Study on uniaxial tensile and low-cyclic fatigue behaviour of Polyamide 12 fabricated by Multi-Jet Fusion - Ng, Wei Hong (Nanyang Technological University, 2022)
The MultiJet Fusion technology (MJF) is a subset of Additive Manufacturing, developed by Hewlett-Packard Development Company, L.P, commonly known as HP. It is undergoing intensive research as I am writing this report. The MultiJet Fusion technology was introduced to the market in 2016 and is meant to produce large batches with high functional complexity while reducing unit costs. However, it is discovered that the construction orientation affects the fatigue performance of the printed PA12 specimen, such as in X-orientation (horizontal) and Z-orientation (vertical). Hence, this project aims to study the anisotropic mechanical properties and fatigue behaviour of the MJF PA12 that are specifically built in different orientations as well as to study the mechanical properties of PA12 by Multi-Jet Fusion based on fatigue analysis. Experiments would be conducted with tensile and fatigue with a holding time. Lastly, the failure surface of specimens are analysed by Optical Microscopy and Scanning Electron Microscopy (SEM) to analyse the void morphology, void distribution, and sintering interfaces. The porosity and void findings performed by Micro-CT are attached in the appendix.